COMPARISON OF PHYSICAL QUALITY OF BALI BEEF PRODUCTED IN BADUNG AND BULELENG SLOUGHTERHOUSE - Septyawati, Gadis Ayu; Swacita, Ida Bagus Ngurah; Suada, I Ketut (Buletin Veteriner Udayana, 2023)
The physical quality of meat is a very important thing that must be considered as a result of the production of an Slaughterhouse, because good physical quality produces quality meat that is fit for consumption. The purpose of this study was to determine the physical quality of Bali beef produced by RPH Badung and Buleleng. This study examines the quality of the meat produced by taking samples from two abattoirs, namely Badung and Buleleng. Meat samples were taken from the thigh region of the femoral region, each sample was taken as much as ± 100 grams. Beef samples were tested for their physical quality for color, smell, texture and consistency using 10 panelists who had met the requirements. The data obtained were analyzed by using the Wilcoxon signed test to see if there was a difference between the two meat samples taken from the Badung and Buleleng abattoirs. The results showed that the color and texture of beef from the Mambal, Badung and Panji Anom slaughterhouses, Buleleng were significantly different (P<0.05). Meanwhile, the consistency was significantly different (P<0.01). However, there was no significant difference in the smell of beef from the Mambal, Badung and Panji Anom abattoirs, Buleleng (P>0.05). It can be concluded that the physical quality of beef produced by RPH Mambal, Badung and Panji Anom, Buleleng is different, except that the smell of the meat is the same.